Aspects of cognition that impact aging‐in‐place and long‐term care planning - Lindquist, Lee A.; Miller‐Winder, Amber P.; Schierer, Allison; Murawski, Alaine; Opsasnick, Lauren; Curtis, Laura M.; Kim, Kwang‐Youn; Ramirez‐Zohfeld, Vanessa (Journal of the American Geriatrics Society (JAGS), 2022)
Older adults frequently defer decisions about their aging-in-place/long-term care (AIP-LTC) needs. As a result, when older adults experience worsening Alzheimer's disease, family members/friends become surrogate decision makers. We sought to understand what aspects of cognition impact older adult AIP-LTC planning. As part of the PlanYourLifespan (PYL)-LitCog study, we longitudinally examined AIP-LTC decision-making among a cohort (LitCog) of community-based older adults (65 years and older) recruited from hospital-associated primary care clinics in Chicago, Illinois, with extensive cognitive testing. PlanYourLifespan.org (PYL) is an evidence-based online intervention that facilitates AIP-LTC planning. Subjects underwent baseline testing, received the PYL online intervention, and then were surveyed at 1, 6, and 12 months about AIP-LTC decision-making. Cross-sectional logistic regression analysis was conducted examining cognitive variables that impacted AIP-LTC decision-making. Of the 293 older adults interviewed (mean age 73.0 years, 40.4% non-White), subjects were more likely to have made AIP-LTC decisions if they had adequate inductive reasoning (ETS letter sets total-OR = 1.14 (95% CI = 1.03-1.27; p < 0.05)) and adequate working memory (size judgment span total-OR = 1.76 (95% CI = 1.13-2.73; p < 0.05)). There were no differences in decision-making observed in verbal abilities, long-term memory, or processing speed. All analyses were adjusted for participant gender, race, age, and decision-making response at baseline. Inductive reasoning and working memory are critical to AIP-LTC decision-making. Screening routinely for these specific cognitive domains is important in targeting and helping older adults prepare in time for their future AIP-LTC needs.